2021
DOI: 10.3389/fmicb.2021.678319
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Shallow Whole-Metagenome Shotgun Sequencing as a High-Accuracy and Low-Cost Method by Complicated Mock Microbiomes

Abstract: Characterization of the bacterial composition and functional repertoires of microbiome samples is the most common application of metagenomics. Although deep whole-metagenome shotgun sequencing (WMS) provides high taxonomic resolution, it is generally cost-prohibitive for large longitudinal investigations. Until now, 16S rRNA gene amplicon sequencing (16S) has been the most widely used approach and usually cooperates with WMS to achieve cost-efficiency. However, the accuracy of 16S results and its consistency w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 24 publications
1
28
0
1
Order By: Relevance
“… Jiang et al (2016) reported an increase of Actinomyces graevenitzii in the salivary microbiota of caries children by applying 16S rRNA sequencing, while no increase but mild decrease of Actinomyces graevenitzii was observed in our study. The probable explanation is that 16S rRNA sequencing and shotgun sequencing has different consistency and accuracy, especially at the species level ( Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… Jiang et al (2016) reported an increase of Actinomyces graevenitzii in the salivary microbiota of caries children by applying 16S rRNA sequencing, while no increase but mild decrease of Actinomyces graevenitzii was observed in our study. The probable explanation is that 16S rRNA sequencing and shotgun sequencing has different consistency and accuracy, especially at the species level ( Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shallow shotgun metagenomic (SSM) sequencing has been the subject of only a few studies so far [11][12][13] and focused mainly on the correlation between SSM and 16S rRNA amplicon sequencing. They were done with artificial datasets or executed with reads-based bioinformatics methods, avoiding the de novo co-assembly process inherent to HRSM workflows.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, these extensive cohort studies should be multi-ethnic as ethnicity has been shown to play an important role in gut microbial profiles [12,13]. Moreover, microbial sequencing techniques should focus more on shotgun metagenomic sequencing to better understand the functional profile of the microbial community, rather than being stuck at the compositional level [111]. This is becoming more realistic as shotgun metagenomic sequencing and mass spectrometry have become more affordable.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%